2018
DOI: 10.1002/jcsm.12340
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between endothelial function and skeletal muscle strength in community dwelling elderly women

Abstract: BackgroundThe aim of this study is to determine whether there is correlation between endothelial function and skeletal muscle function measured by hand grip strength in elderly women.MethodsThis cross‐sectional study used data of NAMGARAM‐2 cohort. The NAMGARAM‐2 cohort consisted of a group of people living in three rural communities. They were enrolled for studies on activity limitation due to age‐related musculoskeletal disorders including knee osteoarthritis, osteoporosis, and sarcopenia. They were resident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 31 publications
0
40
1
Order By: Relevance
“…All 33 studies were either cross-sectional or randomized controlled trials published within the past 10 years (Table 1). Twenty-three studies [20,26,27,[33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52] included healthy mixed-age adults (age range 18-95) and two studies [53,54] included healthy community-dwelling older adults (age range [65][66][67][68][69][70][71][72][73][74][75][76][77][78][79][80][81]. Six studies sampled participants with hypertension [55][56][57][58][59][60], one study sampled individuals with diabetes as a comparator to healthy aged popula...…”
Section: Study Details and Sample Demographicsmentioning
confidence: 99%
See 3 more Smart Citations
“…All 33 studies were either cross-sectional or randomized controlled trials published within the past 10 years (Table 1). Twenty-three studies [20,26,27,[33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52] included healthy mixed-age adults (age range 18-95) and two studies [53,54] included healthy community-dwelling older adults (age range [65][66][67][68][69][70][71][72][73][74][75][76][77][78][79][80][81]. Six studies sampled participants with hypertension [55][56][57][58][59][60], one study sampled individuals with diabetes as a comparator to healthy aged popula...…”
Section: Study Details and Sample Demographicsmentioning
confidence: 99%
“…Study populations varied from a minimum of 6 [20] to a maximum of 3356 [42] participants. Eight studies included only men [25,27,37,42,49,50,56,61] and four studies included only women [38,52,53,60]. Most studies reported the age range of the participants, except for two studies with one claiming to study "middle-aged" adults [46] and one using adult participants [62].…”
Section: Study Details and Sample Demographicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients with CVD develop heart failure symptoms at a high rate, leading to decreased peripheral blood fl ow, chronic infl ammation [27], decreased physical activity [33] and malnutrition [34], which may cause skeletal muscle disorder and decreased physical function [35]. On the other hand, decreased physical function may increase the incidence of cardiovascular events due to decreased balance ability [36] and vascular endothelial Dysfunction [37]. In this study, the depressive tendency determined by HADS was considered to be an independent determinant of physical function, suggesting that physical function declines due to the combination with depressive tendency.…”
Section: Discussionmentioning
confidence: 99%